Reconhecimento e memória: um estudo sobre cegueira botânica e os azulejos do Centro Histórico de São Luís – MA - DOMINICI, Susana dos Santos (2021)
The capital of the Maranhão state, São Luís, has a rich collection of tiles on the facades of the colonial houses. Among the numerous models, many of them have illustrations of floral elements and foliage. However, few botanical patterns are perceived and valued by people, a characteristic known as “plant blindness,” term created by (WANDERSEE e SCHUSSLER, 1999). Cognitive Ergonomics seeks to understand how our perceptual skills work and respond to stimuli, seeking to understand how an environment can affect our mind, in which the reliability of cognition becomes a central issue. These skills are a combination of skills, experience, pattern recognition, attention, memory, the ability to classify information, and more. The present work aims to study and understand if visitors to the Historical Center of São Luís - MA recognize the patterns of tiles existing in old mansions and what is the degree of perception of them to identify the floral patterns existing in some tiles. The conceptual model by Agost and Vergara (2010) was used like theoretical base for the application of the questionnaires and the semantic differential scale contributed on the analysis of the informations. The results showed that the people have a certain identification with the tiles, but without the main emphasis to their botanical drawings. Was verified that the portuguese tiles with stylized phytomorphic prints, as they are the most present in the city, were also considered as more familiar to the participants, making a connection with the visual memories that they had of them.